Multimedia and Network Information Systems Proceedings of the 11th International Conference MISSI 2018 - Choroś, Kazimierz; Kopel, Marek; Kukla, Elżbieta; Siemiński, Andrzej (Advances in Intelligent Systems and Computing,, 2019)
These proceedings collect papers presented at the 11th International Conference on Multimedia & Network Information Systems (MISSI 2018), held from 12 to 14 September 2018 in Wrocław, Poland. The keynote lectures, given by four outstanding scientists, are also included here. The Conference attracted a great number of scientists from across Europe and beyond, and hosted the 6th International Workshop on Computational Intelligence for Multimedia Understanding as well as four special sessions. The majority of the papers describe various artificial intelligence (AI) methods applied to multimedia and natural language (NL) processing; they address hot topics such as virtual and augmented reality, identity recognition, video summarization, intelligent audio processing, accessing multilingual information and opinions, video games, and innovations in Web technologies. Accordingly, the proceedings provide a cutting-edge update on work being pursued in the rapidlyevolving field of Multimedia and Internet Information Systems. .